A randomized trial of adapted versus standard versions of the Transdiagnostic Intervention for Sleep and Circadian Dysfunction implemented via facilitation and delivered by community mental health providers: improving the “fit” of psychological treatments by adapting to context - Allison G. Harvey; Emma R. Agnew; Rafael Esteva Hache; Julia M. Spencer; Marlen Diaz; Estephania Ovalle Patino; Anne Milner; Lu Dong; Amy M. Kilbourne; Daniel J. Buysse; Catherine A. Callaway; Laurel D. Sarfan (Implementation Science)
Abstract Background Grounded in the Integrated Promoting Action on Research Implementation in Health Services framework (i-PARIHS) and the Replicating Effective Programs framework (REP), the goal is to determine if the use of theory, data and end-user perspectives to guide an adaptation of the Transdiagnostic Intervention for Sleep and Circadian Dysfunction (TSC) yields better outcomes and improves the “fit” of TSC to community mental health centers (CMHCs), relative to the standard version. Methods Ten counties in California were cluster-randomized by county to Adapted or Standard TSC. Within each county, adults who exhibited sleep and circadian dysfunction and serious mental illness (SMI) were randomized to immediate TSC or Usual Care followed by Delayed Treatment with TSC (UC-DT). Facilitation was the implementation strategy. The participants were 93 CMHC providers who delivered TSC (Standard = 30; Adapted = 63) and 396 CMHC patients (Standard = 74; Adapted = 124; UC-DT = 198). Patient assessments were completed at pre-treatment, post-treatment, and six months after treatment (6FU). Provider assessments were completed at post-training, mid-treatment, and post-treatment. Results TSC (combining Adapted and Standard), relative to UC-DT before delayed treatment with TSC, was associated with improvement from pre- to post-treatment in sleep disturbance (b = -10.91, p < 0.001, d = -1.52), sleep-related impairment (b = -9.52, p < 0.001, d = -1.06), sleep health composite (b = 1.63, p < 0.001, d = 0.95), psychiatric symptoms (b = -6.72, p < 0.001, d = -0.52), and overall functional impairment (b = -5.12, p < 0.001, d = -0.71). TSC’s benefits for functional impairment and psychiatric symptoms were mediated by improvements in sleep and circadian problems. Adapted versus Standard TSC did not differ on provider ratings of fit and better fit did not mediate the relation between TSC condition and patient outcome. Conclusions TSC can be delivered by CMHC providers. Adapted and Standard TSC both fit the CMHC context. These findings are interpreted through the lens of the four core constructs of the i-PARIHS framework. Trial registration Clinicaltrials.gov identifier: NCT04154631. Registered on November 6, 2019. https://clinicaltrials.gov/ct2/show/NCT04154631